2016
DOI: 10.1155/2016/8675905
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Endogenous Catalase in Macrophage Polarization in Adipose Tissue

Abstract: Macrophages are important components of adipose tissue inflammation, which results in metabolic diseases such as insulin resistance. Notably, obesity induces a proinflammatory phenotypic switch in adipose tissue macrophages, and oxidative stress facilitates this switch. Thus, we examined the role of endogenous catalase, a key regulator of oxidative stress, in the activity of adipose tissue macrophages in obese mice. Catalase knockout (CKO) exacerbated insulin resistance, amplified oxidative stress, and acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
(54 reference statements)
2
21
0
Order By: Relevance
“…Ho and colleagues, the originators of the mice used in the present study, showed increased hydrogen peroxide production by tissue from Cat -/- mice [10]. Park and colleagues demonstrated elevated nitrotyrosine expression in epididymal white adipose tissue of Cat -/- mice [47]. Reactive oxygen species are abundantly produced in obesity and metabolic syndrome [5] and adipose tissue proteins of obese patients have been found to be more carbonylated (a marker of oxidative stress) [63].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ho and colleagues, the originators of the mice used in the present study, showed increased hydrogen peroxide production by tissue from Cat -/- mice [10]. Park and colleagues demonstrated elevated nitrotyrosine expression in epididymal white adipose tissue of Cat -/- mice [47]. Reactive oxygen species are abundantly produced in obesity and metabolic syndrome [5] and adipose tissue proteins of obese patients have been found to be more carbonylated (a marker of oxidative stress) [63].…”
Section: Discussionmentioning
confidence: 95%
“…Notably, crown-like structures, reflective of macrophages surrounding dying or dead adipocytes, are commonly observed in the adipose tissue of ob/ob and db/db mice and are thought to be associated with insulin resistance [46]. A recent study showed higher levels of plasma free fatty acids and triglycerides in Cat -/- mice [47], reaffirming a potential role for catalase in lipid mobilization. The same study also revealed increased numbers of crown-like structures in white adipose tissue in Cat -/- mice, but only under conditions of a high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to obesity, a mouse model expressing mitochondria specific catalase on a high fat diet displayed attenuated mitochondrial ROS emission, preserved insulin signaling, and no inflammatory response compared to wild type controls [11]. This may be because overexpression of endogenous catalase was shown to regulate the polarization of macrophages within adipose tissue and thereby inhibiting inflammation and insulin resistance [31]. On the other hand, mice devoid of antioxidant catalase developed an obese, prediabetic phenotype that was exacerbated with age [32].…”
Section: Introductionmentioning
confidence: 99%
“…CAT is one of the major endogenous antioxidant enzymes that detoxify the reactive oxygen species (ROS) hydrogen peroxide (H2O2) to water and oxygen. While brain CAT activity is low compared to other tissues and organs [25], this enzyme regulates macrophage polarization in adipose tissue [82]. Overexpression of catalase is beneficial in the context of obesity.…”
Section: Ros-related Gene Expression Between Ptsd Patients and Controlsmentioning
confidence: 99%